In vitro embryo production in cattle and buffalo: present status, challenges and outlook - NANDI, S; RAGHU, H R; RAVINDRANATHA, B M; CHAUHAN, M S (The Indian Journal of Animal Sciences, 2014)
The success rate and the practical application of IVP embryos in bovine have not largely increased because of their low efficiency. The production of bovinc cmbryos in vitro is characterized by high rate of maturation (cattle: 85-90%, buffalo: 70-90%), fertilization (cattle: 70-90%, buffalo 60-70%) and cleavage (cattle: 50-80%, buffalo: 40-50%) and moderate to low rate of blastocyst formation (cattle: 30-60%, buffalo: 15-30%) and calf production following transfer (cattle: 101 15%, buffalo: 10.5’%).